2022
DOI: 10.1039/d1sc05681f
|View full text |Cite
|
Sign up to set email alerts
|

GlyNet: a multi-task neural network for predicting protein–glycan interactions

Abstract: Advances in diagnostics, therapeutics, vaccines, transfusion, and organ transplantation build on a fundamental understanding of glycan-protein interactions. To aid this, we developed GlyNet, a model that accurately predicts interactions (relative...

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 65 publications
0
10
0
Order By: Relevance
“…We suggest the use of DeepFRI (53), a deep learning model that predicts protein function, to first determine if the protein is a carbohydrate binding protein. If the protein is a carbohydrate binding protein, then LectinOracle(41) or GlyNet (42) can be used to predict which carbohydrates bind the protein. CAPSIF can then predict binding locations, either from an experimental structure or AF2 generated structures, and then GlycanDock(24) can predict a docked protein-carbohydrate structure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We suggest the use of DeepFRI (53), a deep learning model that predicts protein function, to first determine if the protein is a carbohydrate binding protein. If the protein is a carbohydrate binding protein, then LectinOracle(41) or GlyNet (42) can be used to predict which carbohydrates bind the protein. CAPSIF can then predict binding locations, either from an experimental structure or AF2 generated structures, and then GlycanDock(24) can predict a docked protein-carbohydrate structure.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the physiological response and determining a glycomimetic drug to neutralize the infection requires residue-level knowledge (40). Currently, DL algorithms LectinOracle (41) and GlyNet (42) predict lectin-carbohydrate binding on a protein level; however, pharmaceutical development requires residue-level information.…”
Section: Introductionmentioning
confidence: 99%
“…Other approaches have used glycan-binding data from glycan arrays, where lectins are probed for their binding to immobilized glycans on a glass slide . One example for this would be GlyNet, a neural network-based approach for using the motifs that occur in a glycan to predict its binding to the lectins that have historically been assayed on the CFG platform. Combining interpretable, rule-based machine learning with expert annotation has also recently resulted in the detailed elucidation of the binding motifs of a large set of commonly used lectins .…”
Section: Next-generation Machine Learningmentioning
confidence: 99%
“…7 . It is observed, there are 13 studies including ( Chien et al, 2020 ; Taherzadeh et al, 2019 ; Liu et al, 2019 ; Li et al, 2019 ; Thomès, Burkholz & Bojar, 2021 ; Pitti et al, 2019 ; Adolf-Bryfogle et al, 2021 ; Park et al, 2019 ; He, Wei & Zou, 2019 ; Audagnotto & Dal Peraro, 2017 ; Mondragon-Shem et al, 2020 ; Dimeglio et al, 2020 ; Ruiz-Blanco et al, 2017 ) which have developed the tool specific to the N-Linked site identifications, few studied developed tool for glycosylation sites identification irrespective of the specific type including ( Bojar et al, 2021b ; Carpenter et al, 2022 ; Lundstrøm et al, 2022 ; Burkholz, Quackenbush & Bojar, 2021 ; Coff et al, 2020 ; Shek, Kotidis & Betenbaugh, 2021 ) and some authors ( Le, Sandag & Ou, 2018 ; Liu et al, 2021 ; Yang et al, 2019 ; Campbell, 2017 ) develop tool without mentioning the type of PTM. These all tools have list down in the Table 9 .…”
Section: Assessment Of Q2mentioning
confidence: 99%
“…It is important to specify for which kind of species these tools will be operating, therefore to achieve this purpose the information is also extracted from the selected studies. Some authors ( He, Wei & Zou, 2019 ; Audagnotto & Dal Peraro, 2017 ; Shek, Kotidis & Betenbaugh, 2021 ; Carpenter et al, 2022 ) did not mention the organism type while other mentioned it and it is observed most of them use human data for site identification as mention in Table 9 .…”
Section: Assessment Of Q2mentioning
confidence: 99%